Molecular Identification of Mungbean yellow mosaic virus Infecting Yard Long Beans and Aclypha indica in Kediri, East Java - Effi Alfiani Sidik; Sedyo Hartono; Sri Sulandari (Nusantara Science and Technology Proceedings, 2022)
Mungbean yellow mosaic virus (MYMV) is a Begomovirus species that causes yellow disease in legumes, particularly yard-long beans. Acalypha indica (Euphorbiaceae) is a weed that thrives in yard-long beans fields. Information on these weed species that are naturally infected is needed so that they can serve as MYMV reservoirs. This study aims to determine the MYMV's symptoms, molecular evidence, and diversity. Purposive sampling was used to obtain leaf samples, followed by molecular detection using specific primers, phylogenetic analysis with BioEdit v.7.0.5, and MEGA X version 10.2.6 based on the Neighbor-Joining (NJ) approach. In Kediri, the incidence of yellow mosaic diseases on yard-long beans is nearly 100%, with systemic symptoms such as yellowing, yellow mosaic, mosaic with a yellow-green pattern, leaf malformation, and stunting. Mosaic symptoms are present in several A. indica. The CTAB method was used to isolate total DNA, yielding a concentration of ±100 ng with ? DNA as a comparison. Specific primers (AC2-F & AC2-R) have successfully amplified MYMV in yard-long beans and A. indica. Phylogenetic analysis revealed that the MYMV from Kencong was most closely related to the Mungbean yellow mosaic India virus (MYMIV) from soybean-Brebes and cowpea-Purwakarta. The phylogenetic tree shows bootstrap value in 94 of 1000 iterations between isolates and in a single cluster.